2020
DOI: 10.1016/j.jval.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of RAS Genetic Testing Strategies in Patients With Metastatic Colorectal Cancer: A Systematic Review

Abstract: Background: Monoclonal antibodies against epidermal growth factor receptor (EGFR) have proved beneficial for the treatment of metastatic colorectal cancer (mCRC), particularly when combined with predictive biomarkers of response. International guidelines recommend anti-EGFR therapy only for RAS (NRAS, KRAS) wild-type tumors because tumors with RAS mutations are unlikely to benefit. Objectives:We aimed to review the cost-effectiveness of RAS testing in mCRC patients before anti-EGFR therapy and to assess how we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Pharmacogenetic analysis as a strategic tool focused on Precision Medicine is a practice that has expanded into specialized fields such as Oncology. 7 Knowledge of the patient's pharmacogenotype has proved useful when considering certain treatments based on the genetic nature of certain pathologies and has in some cases been able to reduce the costs associated with hospitalizations, adverse effects and pharmacotherapies not adjusted to the pharmacokinetic and/or pharmacodynamic of the patient. [8][9][10][11][12][13][14][15][16][17][18] There is some evidence to suggest that controlling the dose of various drugs guided by the patient's genotype could reduce the costs of morbidity and mortality associated with drugs that have, in the United States alone, exceeded $177B.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenetic analysis as a strategic tool focused on Precision Medicine is a practice that has expanded into specialized fields such as Oncology. 7 Knowledge of the patient's pharmacogenotype has proved useful when considering certain treatments based on the genetic nature of certain pathologies and has in some cases been able to reduce the costs associated with hospitalizations, adverse effects and pharmacotherapies not adjusted to the pharmacokinetic and/or pharmacodynamic of the patient. [8][9][10][11][12][13][14][15][16][17][18] There is some evidence to suggest that controlling the dose of various drugs guided by the patient's genotype could reduce the costs of morbidity and mortality associated with drugs that have, in the United States alone, exceeded $177B.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,18 For example, testing mCRC patients for RAS status and treating only patients without RAS mutations with EGFR inhibitors are more cost-effective than treating all patients without testing. 19 Despite the increased interest in the utilization of NGS and its utility to identify patients to match with clinical trials, 8,9 underrepresentation of racially diverse patients in clinical trials has persisted. [20][21][22][23][24] Our findings, showing disparities in biomarker testing, point to potential further exacerbation of disparities in targeted therapy and clinical outcomes among those with mCRC and in clinical trial participation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the identification of tumor alterations can provide targeted therapy, thus improving clinical outcomes. 17 Indeed, the ability of biomarkers to improve treatment and reduce costs has been previously demonstrated, 18 , 19 including sparing patients from futile, potentially toxic and expensive treatment. 13 , 14 , 18 For example, testing mCRC patients for RAS status and treating only patients without RAS mutations with EGFR inhibitors are more cost‐effective than treating all patients without testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthy to note that to cater to more effective targeted therapy in CRC subjects, genetic testing to identify mutational profiles, including MSI status and both p53 and KRAS mutations, is required. In many countries, the cost for mutational screening is considered expensive and may not be accessible to the majority of the population due to a lack of technologies and facilities [ 104 ]. This hinders the progress of targeted gene therapy in CRC.…”
Section: Challengesmentioning
confidence: 99%